2017
DOI: 10.5005/jp-journals-10028-1226
|View full text |Cite
|
Sign up to set email alerts
|

Steroid-induced Glaucoma: An Avoidable Irreversible Blindness

Abstract: Steroids are a group of anti-inflammatory drugs, commonly used to treat ocular and systemic conditions. Unmonitored use of steroids especially in eye drop formulations is common in situations when it is easily available over-the-counter, resulting in undesirable side effects.Among the ocular side effects, cataract and glaucoma are common. Steroid-induced ocular hypertension was reported in 1950, when long-term use of systemic steroid was shown to increase the intraocular pressure (IOP). Chronic administration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
90
0
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(102 citation statements)
references
References 49 publications
3
90
0
9
Order By: Relevance
“…Similar to other corticosteroid treatments [ 22 ], increases in IOP may occur with the dexamethasone intracanalicular insert [ 6 ]. Monitoring IOP is recommended during treatment with the dexamethasone intracanalicular insert, and caution is advised if the dexamethasone intracanalicular insert is used in patients with glaucoma [ 6 ].…”
Section: Tolerability Of the Dexamethasone Insertmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to other corticosteroid treatments [ 22 ], increases in IOP may occur with the dexamethasone intracanalicular insert [ 6 ]. Monitoring IOP is recommended during treatment with the dexamethasone intracanalicular insert, and caution is advised if the dexamethasone intracanalicular insert is used in patients with glaucoma [ 6 ].…”
Section: Tolerability Of the Dexamethasone Insertmentioning
confidence: 99%
“…4 ). Although elevated IOP is associated with use of topical corticosteroids [ 22 ], increases in IOP AEs with the dexamethasone intracanalicular insert were limited to day 2 (i.e. 1 day after surgery).…”
Section: Current Status Of the Dexamethasone Intracanalicular Insert mentioning
confidence: 99%
“…Several studies have reported congenital renal anomalies as the most common renal diagnosis. [2,5,6,19,20] In this research, the congenital renal abnormalities were the second most frequent renal disease. Congenital, hereditary, and genetic renal disease can be attributed to the high prevalence of parental consanguinity in the Jordanian community although there is a declining trend in consanguinity: "The level of consanguinity decreased from 57% in 1990 to 35% in 2012, according to the Jordan Population and Family Health Surveys."…”
Section: Discussionmentioning
confidence: 66%
“…It is known that topical, periocular, and even systemic or inhaled administration of steroids can cause OH [91]. The significant elevation of the IOP can occur in a matter of hours or up to 1 day after steroid use.…”
Section: Models Of Ocular Hypertension (Oh)mentioning
confidence: 99%